Modern families : stories of extraordinary journeys to kinship - Gamson, Joshua, 1962- (New York University Press, 2015)
The kinds of families we see today are different than they were even a decade ago as paths to parenthood have been rejiggered by technology, activism, and law. Gamson brings us extraordinary family creation tales that illuminate this changing world of contemporary kinship. He tells a variety of unconventional family-creation tales-- adoption and assisted reproduction, gay and straight parents, coupled and single, and multi-parent families-- set against the social, legal, and economic contexts in which they were made.